1989
DOI: 10.1073/pnas.86.19.7634
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin 1, an endothelium-derived peptide, is expressed in neurons of the human spinal cord and dorsal root ganglia.

Abstract: Endothelin 1, an endothelium-derived peptide, is expressed in neurons of the human spinal cord and dorsal root ganglia ( ABSTRACTThe localization of endothelin 1 mRNA and endothelin-like immunoreactivity was investigated in samples of neurologically normal nervous system tissue from 10 adults by using in situ hybridization and immunocytochemistry. Tissue sections of spinal cord and dorsal root ganglia were hybridized with an 35S-radiolabeled endothelin 1 complementary RNA probe. Autoradiograms showed labeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
132
0
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(140 citation statements)
references
References 14 publications
5
132
0
3
Order By: Relevance
“…The sequence of preproET-1 deleted in Stop9l contains a cysteine-rich ET-1-like domain of 15 amino acids with 8 conserved residues. It has been suggested that ET-1 might have an endocrine function as a neuropeptide or neuromodulator (19) and could be stored in secretory granules in the posterior pituitary (20). ET-1 is encoded by a single gene (21) and is expressed in widely different cell types (2), some of which are endowed with a regulated secretory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of preproET-1 deleted in Stop9l contains a cysteine-rich ET-1-like domain of 15 amino acids with 8 conserved residues. It has been suggested that ET-1 might have an endocrine function as a neuropeptide or neuromodulator (19) and could be stored in secretory granules in the posterior pituitary (20). ET-1 is encoded by a single gene (21) and is expressed in widely different cell types (2), some of which are endowed with a regulated secretory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…High-affinity receptor sites for ET are found in the central nervous system (Giaid et al, 1989;Jones et al, 1989;Koseki et al, 1989) and ET-mediated Ca2+ responses have been demonstrated in neurons as well as in glial cells in culture (Fu et al, 1989;Supattapone et al, 1989;Lin et al, 1990a;MacCumber et al, 1990;Marsault et a]., 1990;Stojilkovic et al, 1990;Zhang et al, 1990). Studies by MacCumber et al (1 990) have suggested that ET in brain is produced largely by the glial cells, but it can act on both glia and neurons in a paracrine fashion.…”
mentioning
confidence: 99%
“…ET-1, başlıca damar endotelinde sentezlenlenip salıverilmekte ve burada damar geriminin düzenlenmesini sağlamaktadır. Bunun dışında, mast hücreleri, makrofajlar, mukozal epiteliyum, kardiyomiyositler, nöronlar, trakea epiteli, renal medulla, hepatik sinüzoitler ve Kuppfer hücrelerinde de sentezlenmektedir (39)(40)(41)(42)(43)(44). Vücutta daha az dağılım gösteren ET-2 böbrek ve bağırsaklarda bulunurken; ET-3 ise beyin, akciğer, bağırsak ve adrenal bezde bulunmaktadır (45)(46).…”
Section: Toll-interleukin 1 Receptor Domain-containing Adapter-induciunclassified